2020
DOI: 10.1007/s10902-020-00264-2
|View full text |Cite
|
Sign up to set email alerts
|

The Bigger the Better? Business Size and Small-Business Owners’ Subjective Well-Being

Abstract: Business growth is often portrayed as an important outcome for small-business owners. Few empirical studies have however examined whether there is a positive relationship between business size and different dimensions of small-business owners’ subjective well-being. In a large cross-sectional sample (n = 1089) of small-business owners from Sweden, we investigate the relationship between business size and the two main components of subjective well-being, life satisfaction and emotional well-being. By means of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Participants also identified that their job satisfaction was quite high, further supporting previous literature on small business owners more broadly, who often report having high job satisfaction (e.g. Fors Connolly et al, 2020). The interviews provided some elaboration on areas that need to be improved in relation to their mental health and wellbeing including the challenges of being a small business owner and lack of social connection with other educators.…”
Section: Discussionsupporting
confidence: 78%
“…Participants also identified that their job satisfaction was quite high, further supporting previous literature on small business owners more broadly, who often report having high job satisfaction (e.g. Fors Connolly et al, 2020). The interviews provided some elaboration on areas that need to be improved in relation to their mental health and wellbeing including the challenges of being a small business owner and lack of social connection with other educators.…”
Section: Discussionsupporting
confidence: 78%
“…Xu et al (2021) associate the happiness with institutional trust, emphasizing the influence of external operating environment on the happiness of entrepreneurs as well. Carree and Verheul (2012) believe that income, mental stress, and leisure time are important factors affecting happiness, and Filip et al (2020) come to a similar conclusion.…”
Section: Research Background and Literature Reviewmentioning
confidence: 91%